An end-to-end framework for context-aware business process outsourcing to the cloud. (October 2017) - Rekik, Mouna; Boukadi, Khouloud; Ben-Abdallah, Hanêne
Highlights: A System for assisting business process outsourcing to the cloud is proposed. The system considers the dynamic business process context posterior and prior of the outsourcing. An extension of the CloudSim is illustrated to support the business process execution simulations. The system relies on NSGA II optimization algorithm to minimize costs, response time and risks. Graphical abstract: Abstract: Highly motivated by the advantages of cloud computing, enterprises are considering outsourcing their business processes to the cloud to reduce their cost, increase their flexibility, and enhance their performance. The purpose of this paper is to propose a comprehensive end-to-end framework for business process outsourcing to the cloud, that considers the dynamic business process context. The framework comprises different methods able to efficiently take into account accurate and up-to-date business process context to identify the best process fragment to outsource and the most suitable cloud service to adopt. The optimality of the identified solutions is insured by NSGA II (Elitist Non-Dominated Sorting Genetic Algorithm) for which we proposed a set of context-based objective functions. In addition, the framework considers the business process context prior and post the outsourcing decision in order to change a decision to account for context changes. The performance of the framework is experimentally illustrated.